Analogy to different things and objects in the works of Abdulla Qahhor (Eurasian Journal of Humanities and Social Sciences, 2023)
The analogy serves as a basis for drawing scientific, philosophical, social, spiritual and enlightenment conclusions. Simulation is extremely important in the development of human thinking. This article discusses the skill of analogy and its role in the polishing of human speech, especially the skill of using analogy in Abdullah Qahhor’s stories, based on the analysis of the stories.